Do administrative databases accurately measure waiting times for medical care? Evidence from general surgery - Coster, Carolyn De (Canadian Medical Association, 2007)
We abstracted the records of patients from general surgeons' offices in Winnipeg to compare waiting times from charts (i.e., the gold standard) with waiting times using administrative data. The administrative data method relies on physicians' billing data to identify a visit to the surgeon preoperatively to mark the start of the waiting time. There was no difference between waiting times using patient records versus administrative data. The study supported the use of administrative data to monitor waiting times.